1997
DOI: 10.1128/mcb.17.12.6822
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of DNA Interstrand Cross-Link Repair in Humans: the Nucleotide Excision Repair System Makes Dual Incisions 5′ to the Cross-linked Base and Removes a 22- to 28-Nucleotide-long Damage-Free Strand

Abstract: Most DNA repair mechanisms rely on the redundant information inherent to the duplex to remove damaged nucleotides and replace them with normal ones, using the complementary strand as a template. Interstrand cross-links pose a unique challenge to the DNA repair machinery because both strands are damaged. To study the repair of interstrand cross-links by mammalian cells, we tested the activities of cell extracts of wild-type or excision repair-defective rodent cell lines and of purified human excision nuclease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 64 publications
10
102
1
1
Order By: Relevance
“…To explore the origin of the DSBs, their induction in exponentially growing HN2-treated NER disruptant strains was assessed, since available information suggests that this is the pathway which initiates ICL repair (6,29,39). Surprisingly, isogenic disruptant rad4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the origin of the DSBs, their induction in exponentially growing HN2-treated NER disruptant strains was assessed, since available information suggests that this is the pathway which initiates ICL repair (6,29,39). Surprisingly, isogenic disruptant rad4 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We sought to address the reasons for this discrepancy, particularly because existing models of ICL repair generally demand a role for recombination (6,12). Our data clearly show that rad52 sensitivity to HN2 and cisplatin is dependent upon growth phase, with recombination being required only during exponential-phase repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a correlation between the preferred cross-link sequence, structural data, and a subset of the observed mutation spectrum (57). MDA-induced mutations at sites other than 5Ј-(CG) may have arisen as a result of NER-dependent incision of sequences flanking the 5Ј-(CG) ICLs (59,60), through the intermediacy of cross-links at other sequences, or from other MDA-DNA adducts that trigger mutations in an NER-dependent fashion.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to NER-defective mutants in E. coli and yeast, the NER-defective mammalian cells (except for ERCC-1 and ERCC-4 cells) are only moderately sensitive to DNA cross-linking agents such as mitomycin C (MMC) (8 -11). Moreover, biochemical studies demonstrated that the dual incisions by mammalian NER do not "unhook" ICLs (12,13). Therefore, mammalian cells evidently have a unique mechanism(s) to initiate ICL repair.…”
Section: Dna Interstrand Cross-links (Icls)mentioning
confidence: 99%